Adaptation and mitigation strategies in the transportation sector to reduce the greenhouse gases emission in Batu City - Lestari, Juwita Amanda; Boedisantoso, Rachmat; Assomadi, Abdu Fadli (Sustinere: Journal of Environment and Sustainability, 2018)
The increased number of tourists in Batu City has resulted in traffic congestion, which led to the increase of emission contributing to GHGs effect and caused global warming. According to Presidential Regulation Number 71 of 2011, each region is required to conduct a national inventory of GHGs emission, in order to determine the appropriate adaptation and mitigation strategies in reducing the GHG emission. This research aimed to reduce the GHGs emission and to determine the appropriate adaptation and mitigation strategies in Batu City especially in the transportation sector. IPCC Guidelines 2006 was used as the method to calculate GHGs emissions. Such method allowed the researchers to determine the emission level by using secondary data obtained from the relevant institution. Determination upon adaptation and mitigation strategies was on the basis of several scenarios of emission level reduction while the prioritized strategy selection was based on the Analytical Hierarchy Process method. This research revealed that the GHGs emission with business as usual scenario in 2030 contributed by transportation reached 2,072.64 Gg of CO2 while the greatest reduction of GHG emissions amounted to -6.13% taken from the scenario of Intelligent Transport System application. More importantly, the researchers figured out that the prioritized adaptation strategies should be the improvement of Urban Open Space and public transportation rejuvenation for the mitigation.